AI Rehabilitation vs. Traditional Physical Therapy: A Comparative Analysis for the Digital Health Era - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of physical rehabilitation is undergoing a profound transformation, driven by the integration of Artificial Intelligence AI and digital health ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Wearable Technology